2007
DOI: 10.1007/s10549-007-9541-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the two-gene ratio in breast cancer—independent roles for HOXB13 and IL17BR in prediction of clinical outcome

Abstract: Background: The two-gene expression ratio HOXB13:IL17BR has been proposed to predict

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 28 publications
(36 reference statements)
3
42
0
Order By: Relevance
“…Because high HOXB13 and low IL17BR expression levels are associated with recurrence, we proposed that a simple HOXB13:IL17BR two-gene ratio could serve as a novel biomarker for predicting recurrence in breast cancer patients receiving adjuvant tamoxifen therapy. Subsequent studies by us (9, 10) and others (11,12) have shown that HOXB13:IL17BR is both prognostic (i.e., predicts the risk of breast cancer recurrence) and predictive of tamoxifen benefit (i.e., tamoxifen response/resistance).Given the well-established prognostic importance of histologic tumor grade (13) and tumor grade -associated genes (7) in breast cancer, a simple robust gene expression assay for tumor grade would be a valuable clinical tool. Herein, we developed a simple 5-gene tumor grade signature (MGI for molecular grade index) that recapitulates tumor grade and show that it predicts clinical outcome with comparable performance to the wellcharacterized 97-gene tumor grade index.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Because high HOXB13 and low IL17BR expression levels are associated with recurrence, we proposed that a simple HOXB13:IL17BR two-gene ratio could serve as a novel biomarker for predicting recurrence in breast cancer patients receiving adjuvant tamoxifen therapy. Subsequent studies by us (9, 10) and others (11,12) have shown that HOXB13:IL17BR is both prognostic (i.e., predicts the risk of breast cancer recurrence) and predictive of tamoxifen benefit (i.e., tamoxifen response/resistance).Given the well-established prognostic importance of histologic tumor grade (13) and tumor grade -associated genes (7) in breast cancer, a simple robust gene expression assay for tumor grade would be a valuable clinical tool. Herein, we developed a simple 5-gene tumor grade signature (MGI for molecular grade index) that recapitulates tumor grade and show that it predicts clinical outcome with comparable performance to the wellcharacterized 97-gene tumor grade index.…”
mentioning
confidence: 84%
“…Because high HOXB13 and low IL17BR expression levels are associated with recurrence, we proposed that a simple HOXB13:IL17BR two-gene ratio could serve as a novel biomarker for predicting recurrence in breast cancer patients receiving adjuvant tamoxifen therapy. Subsequent studies by us (9, 10) and others (11,12) have shown that HOXB13:IL17BR is both prognostic (i.e., predicts the risk of breast cancer recurrence) and predictive of tamoxifen benefit (i.e., tamoxifen response/resistance).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to prostate cancer, HOXB13 has also been shown to have a role as a tumor suppressor in primary colorectal cancers (CRC; ref. 16), and it predicts breast cancer recurrence (17) and tamoxifen response (18).…”
Section: Introductionmentioning
confidence: 99%
“…The interleukin 17 receptor B (IL17RB or IL17BR) is an estrogen-regulated gene (Wang et al, 2007) and found to be a prognostic marker, together with homeobox 13 expression, for breast cancer (Jerevall et al, 2008;Ma et al, 2008). In general, interleukins, chemokines, cytokines and other immunological molecules are known to play a major role during implantation.…”
Section: Discussionmentioning
confidence: 99%